The Creative Process of Malebba Kacubbu Dance: A Contemporary Children’s Dance Rooted in Bugis Cultural Traditions - Miftahul Jannah (Cita konsultindo, 2025)
This study aims to describe the creative process of the Malebba Kacubbu dance as a contemporary children’s dance work rooted in Bugis cultural values. This dance is an adaptation of the traditional game Malebba Kacubbu, which reflects the spirit of hard work (reso), sportsmanship (pesse), and obedience to rules (mappesona ri ade’). The research was conducted at the Pajoge Andino Art Studio Foundation, Sidrap Regency, South Sulawesi, using a descriptive qualitative method. Data were obtained through observation, interviews, and documentation of the rehearsal and dance creation process involving children aged 10–11 years. The results show that the creative process consists of three main stages: cultural and movement exploration, improvisation, and choreographic composition. This dance work demonstrates an effort to preserve Bugis culture through enjoyable and educational art learning, while at the same time instilling character values in children.